Comparison of technical skills effectiveness of men's national volleyball teams - Patsiaouras, A.; Charitonidis, K.; Moustakidis, A.; Kokaridas, D. (International Journal of Performance Analysis in Sport, 2009)
The purpose of the study was to determine the technical elements that could lead to a prediction to winning or losing a match by taking into account the differences of the technical elements recorded among the teams that participated in the Japan word volleyball championship (Pool B). The sample consisted of 6 national men's teams who competed in the frames of world championship during the 2006 period. The recording was made by using the official statistical logistic package of the European Confederation (CEV). Additional statistical analysis of the results took place by using the SPSS 11 statistical package. Discriminant analysis was conducted to select which subset of the measured variables significantly contributed to the prediction of winning or losing a match. Results showed that "attack error", "jump services point", "quick ball error", and "jump serves", led to the prediction of the match outcome (winning or losing a match) whereas "attack after reception" and "quick ball attack" emerged as the decisive factors for team qualification.